If I had a magic wand: Speculative everyday anti-racism for addressing workplace racial discrimination in British Columbia's public sector - Farid Asey (Social Work & Society, 2023)
Using empirically-derived knowledge from twenty-five interviews with racialized public servants in British Columbia, Canada, this article presents a qualitative exploration of participant-proposed solutions to racial discrimination at work. Participants were selected on the basis of reporting lived experiences with workplace racial discrimination and their insights were collected through in-depth qualitative interviews in response to a speculative question on how they would stomp out the specter of racisms in their workplaces if they had all the power and resources to do so. This study introduces speculative everyday anti-racism as a framework that outlines additional possibilities for resistance, contestation and liberation at work. Speculative everyday anti-racism aims to also offer the discursive and political power to participants and disrupts the practice of experts and academic knowledge-producers providing prescriptions for workplace anti-racist work. The guiding principle behind the design of this study is that if workplaces are to respond effectively to racial discrimination in their midst, racialized workers ought to play a key role in identifying issues and proposing solutions. Thus, it is proposed that a reconceptualization of antidiscrimination grounded on speculative everyday anti-racism could better assist policy makers and practitioners in responding to racial discrimination in the workplace.